Kontestasi Politik dan Rezim Demokrasi Visual di Indonesia - Mr Nyarwi (Program Studi Ilmu Komunikasi, 2010)
Currently the visual democratic regime has been growing as a mode of Indonesian political contestations. Political party, political institution, governance, civil society, and media industries subordinated by the visual democratic regime. This article will examine and reflect that phenomenon. First, this article will examine the visual democratic regime and its impact on practical democracy in Indonesia. Second, this article elaborates the political-economic logic of democracy based on visual democratic regimes. Third, the privatization and personalization of Indonesian political performance facing the national election 2009 will be discussed. Last, this article will explain the public sphere anomaly around the contestations of political performance.